Low cytoplasmic NUB1 protein exerts hypoxic cell death with poorer prognosis in oestrogen receptor negative breast cancer patients - Tan, Ka-Liong; Haider, Syed; Zois, Christos E.; Hu, Jianting; Turley, Helen; Leek, Russell; Buffa, Francesca; Acuto, Oreste; Harris, Adrian L.; Pezzella, Francesco (Translational oncology, 2024)
•1) The study identified that downregulated AIPL1 leads to the deactivation of NUB1 under hypoxic conditions, resulting in cell cycle arrest in breast cancer cells. 2) Low cytoplasmic NUB1 expression is significantly associated with poorer overall survival, particularly in ER-negative breast cancer patients, indicating its potential as a prognostic biomarker. 3) NUB1’s role in preventing cell cycle arrest is crucial, with its absence linked to the upregulation of p21 and p27 and poorer survival outcomes in breast cancer. Current prognostic biomarkers fall short in stratifying Oestrogen receptor (ER)-negative breast cancer patients regarding tumour progression risk at diagnosis. The role of AIPL1 in activating its tumour suppressor client protein, NEDD8 Ultimate Buster-1 (NUB1) remains unknown in cancer. Our study demonstrated how downregulated AIPL1 results in the deactivated NUB1 protein under hypoxic conditions. We examined the AIPL1-NUB1 pathwayin vitro using cell lines i.e. MCF-7, MDA-MB-231, RCC4 etc. NUB1 expression was assessed using Oncomine, and cBioPortal was performed to assess NUB1′s prognostic significance in human cancers. In the John Radcliffe Hospital cohort (n = 122), immunohistochemistry analysis revealed downregulated AIPL1 (Log2 fold change=-0.28; p < 0.001) and upregulated NUB1 transcripts (Log2 fold change=0.59; p < 0.001) compared to adjacent normal tissues. In severe chronic hypoxia, multimerised AIPL1 localisedin the cytoplasm while NUB1 protein migrated to the nucleus, where the absence of NUB1 nuclear localisation led to cell cycle arrest. Biopsies showed that patients with lower cytoplasmic NUB1 expression (n = 57) had poorer overall survival compared to those with higher cytoplasmic expression (n = 57), HR=1.78; 95 % CI=1.01–3.35, p = 0.048. Low NUB1 protein levels in both normoxic and hypoxic conditions were associated with cell cycle arrest and upregulation ofp21 and p27 in breast cancer cell lines, correlating significantly withpoorer survival outcomes in all breast cancer and ER-negative breast cancer patients. [Display omitted]